Peningkatan Ketahanan Terimbas Bawang Merah Terhadap Penyakit Moler Pada Variasi Konsentrasi Spora Agens Hayati Fusarium Oxysporum F. Sp. Cepae Avirulen - Bambang Nugroho; Warmanti Mildaryani (Jurnal Penelitian Pertanian Terapan, 2025)
Moler disease caused by Fusarium oxysporum f. sp. cepae is a main disease on shallot resulting high yield loss and always found in every shallot plantation. Biological control using antagonistic microorganism is an effective method in controlling moler disease with the mode of action of induced resistance. Expression of induced resistance may be affected by several factors such as the concentration of inducer. This research studied the effect of concentration of inducer in increasing induced resistance of shallot to moler disease so that the best contration was revealed. Single factor (spore concentration) with Completely Randomized Design and three replications was used. Spore concentration of avirulent F. oxyssporum f. sp. cepae used in this research was as follows: A = control, B = spore concentration of 104/ml, C = spore concentration of 105/ml, and D = spore concentration of 106/ml. Induced resistance was raised by soaking the shallot bulbs in the spore suspension of the inducer for about 30 minutes. The bulbs were then planted in polybags containing planting media of soil : cow manure with the ration of 1:1 (v/v). The results showed that the treatments were able to increase shallot resistance to moler disease from susceptible to moderate. Regression analysis revealed that the higher the concentration the higher the suppression of moler disease intensity. Increasing suppression of moler disease intensity may increase the growth and yield of shallot.